Interdisciplinary health consultations for older people in Portugal: primary care and hospitals - Maria Clara Duarte Monteiro; Maria Manuela Ferreira Pereira da Silva Martins; Soraia Dornelles Schoeller (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze the perspective of doctors, nurses, and social workers about practices for older people health in primary care and in hospitals; to create guidelines for the practice of interdisciplinary consultations. Method: Cross-sectional study involving 291 professionals from public institutions in the northern region of Portugal. Data were collected between May/2018 and March/2019, using a questionnaire which was then subjected to descriptive and analytical statistical analysis. Results: The usefulness of scales for elderly people showed no differences between hospital and primary care. Hospital professionals collected the following data: eyesight/hearing; medication; direct contact or contact by writing between professionals; daily team meetings; need to share information among colleagues. Primary care professionals, in turn, valued: weight/height, swallowing; the need for home visits; direct contact or via e-mail between professionals; weekly team meetings. Conclusion: The practices of the professionals suggested an intervention model with common aspects in both groups, but with specificities for both primary and hospital care.